Analyzation of the Tawang Health Center’s Implementation of HIV/AIDS Recording and Reporting in Tasikmalaya City: Tinjauan Pelaksanaan Pencatatan dan Pelaporan Kunjungan Pasien HIV/AIDS di Puskesmas Tawang Kota Tasikmalaya - Heriana, Diani Putri; Fauziah, Ulfah (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
A lot of major nations around the world, including Indonesia, struggle with the spread of infectious illnesses. Among the most common infectious diseases that still pose a threat is HIV. The system for tracking and reporting HIV/AIDS patient visits at the Tawang Community Health Center in Tasikmalaya City, which is based on Minimum Service Standards, has achieved 93% of the target, which was set using both an electronic SIHA (HIV/AIDS Information System) application and a manual Microsoft Excel application. Based on Minister of Health Regulation Number 23 of 2022 concerning Management of Human Immunodeficiency Virus, Acquired Immunodeficiency Syndrome, and Sexually Transmitted Infections, the Tawang Community Health Center in Tasikmalaya City uses SIHA version 2.1 for recording and reporting HIV/AIDS patient visits. Targets and accomplishments related to HIV/AIDS are predicated on certain groups of people who are tested for the virus and are listed in the HIV/AIDS Information System (SIHA), specifically the key population. Unstable networks, anonymous patients, and the challenge of reaching risk groups are some of the obstacles encountered.